Surrounding-aware screen-space-global-illumination using generative adversarial network - Mahmud, Abrar; Sifar, Alimus; Rahman, Moh. Absar; Mostafa, Fateen Yusuf; Tasnova, Lamia (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.